A Comparison of Î±-Sutte Indicator and ARIMA Methods in Renewable Energy Forecasting in Indonesia - Saleh Ahmar, Ansari (International Journal of Engineering and Technology, 2018)
Humans in this world are very dependent on petroleum and energy.Â Petroleum and other energies are a major source in supporting human life.Â Regarding the reduced petroleum availability, a new energy is needed to replace the role of petroleum.Â Nowadays, there is much renewable energy that have been discovered and used.Â The purpose of this research is to predict theÂ total primary energy supplyÂ in Indonesia by usingÂ Î±-Sutte Indicator andÂ ARIMAÂ method, and comparing those four methods which are effective in predicting data.Â Data from the research is renewable energy (total primary energy supply) which is obtained from OECD from 1971-2015.Â From the research, it is found that theÂ Î±-Sutte IndicatorÂ method isÂ more suitable to predict renewable energy (total primary energy supply)Â dataÂ in Indonesia compared to ARIMA (0,1,0).Â